Toxicity Test on Wedusan (Ageratum spp.) Extract Against Sitophilus spp. (Coleoptera: Curculionidae) - Mosip, Erinus; Rahardjo, Bambang; Astuti, Ludji (Journal of Tropical Life Science, 2018)
Tropical condition in Southeast Asia has contributed around 30% of post harvest damage as it provide optimum condition for the growth of Sitophilus spp. pest. Therefore, this study was aimed to investigate the effect of wedusan extract on controlling Sitophilus spp. Growth. Wedusan extract was given in different level of concentrations. The research used the Randomized Complete Design. Wedusan (Ageratum spp.) extract affected the imago mortality of Sitophilus spp. There were two kinds of Wedusan extract used in this study, dried extract (DE) and fresh extract (FE).Â  Sitophilus imago were put into bottles filled with organic rice and were treated with Wedusan extract. The mortality level was obsered at 24 Hours After Application (HAA), 48 HAA, and 72 HAA. The highest toxicity was found by the treatment of dried extract of wedusan 5 tablets, by LC50 55% on 24 HAA and 82.25% on 72 HAA. Extract of dry matter has higher toxicity effect than fresh extract. The application of wedusan extract is eviromental friendly and specific-range against pest. It is promising for future development as natural product in agriculture area.